La Compagnie royale d’Afrique et les commerçants négriers anglais sur la baie de Loango (entre 1650 et 1838) - Arsène Francoeur Nganga (Études Caribéennes)
From 1550, the United Kingdom of Great Britain enters into the Atlantic slave trade on the African coasts by venturing first on the coast of Sierra Leone and the Gold Coast (modern Ghana). A century later, English arrive on the coast of the Kingdom of Loango, after a vain attempt on the coast of the colony of Angola monopolized by the Portuguese wanting to defend their monopoly against any form of competition. The Loango coast offered a less expensive trade of good quality; it will become an Eldorado for the royal African company and the slave traders who were essentially English. The rise of Britain as Europe’s leading black ebony power in the 18th century could not have been achieved without their presence on the Loango Coast, an important structure of the 18th century British economy.